Cross-sensitivity of psychiatric and behavioral side effects with antiepileptic drug use. (November 2018) - Chen, Baibing; Choi, Hyunmi; Hirsch, Lawrence J.; Legge, Alexander; Buchsbaum, Richard; Detyniecki, Kamil
Highlights: Psychiatric and behavior side effect (IPBSE) cross-sensitivity rates are compared. Depression and psychosis increase patient risk of experiencing IPBSE to > 2 AEDs. Risk of experiencing IPBSE to LEV or ZNS increases given IPBSE to any other AED. The IPBSE cross-sensitivity rate between LEV and ZNS are particularly high. Abstract: Purpose: To determine rates of cross-sensitivity of intolerable psychiatric and behavioral side effects (IPBSEs) among commonly used antiepileptic drugs (AEDs) in adult patients with epilepsy. Methods: IPBSE was defined as a psychiatric or behavioral side effect attributed to AED use that led to a decrease in dose or cessation of an AED. Cross-sensitivity was calculated and was defined as the likelihood of developing IPBSE to a specific AED given IPBSE to another AED. Our sample consisted of 2312 adult patients that were prescribed 2 or more AEDs. Non-AED confounders and were controlled for in all analyses. Results: Among the 2312 patients, 20.2% of patients who had taken at least 2 AEDs had IPBSE(s) attributed to at least one AED; 3.5% had IPBSE to two or more AEDs. History of treated depression and psychosis were found to be significant predictors (p < 0.001) of developing IPBSE and were controlled for in all AED-specific analyses. Cross-sensitivity was seen between LEV and ZNS (p < 0.001). There was a significant increase in odds of experiencing IPBSE to LEV (41.5%; OR = 2.7; p < 0.001) or ZNS (22.1%; OR = 3.5; p < 0.001) given a patient had IPBSE to another AED compared to having no IPBSE to other AEDs (20.5% and 7.5%, respectively). Conclusion: History of depression and psychosis increased risk of developing IPBSE to AEDs. The probability of experiencing IPBSE increased for a patient taking LEV or ZNS if the patient experienced IPBSE to another AED. Our results may be clinically useful for predicting IPBSE associated with certain AEDs.